Data Journalism. (March 2020) - Lewis, Norman P.; McAdams, Mindy; Stalph, Florian
This syndicate offers four recommendations to help educators adjust curricula to accommodate the rapid integration of data into journalism. First, instruction in numeracy and basic descriptive statistics must be required as either modules in existing courses or as separate offerings. Second, students should be taught to avoid mistakes in interpreting and writing about data in both reporting and visual classes. Third, ethics courses should discuss data as a transparency tool that poses distinctive dilemmas. Fourth, computational thinking, or how to dissect and solve problems like a computer does, can be incorporated into existing classes that teach logic.